2016
DOI: 10.1007/s00128-016-1915-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Contamination in Vegetables Grown Using Paper Mill Wastewater in Wonji Gefersa, Ethiopia

Abstract: Heavy metals are among the major contaminants of vegetables. A study was conducted at Wonji Gefersa farms where paper wastewater is used for cultivation of vegetable crops. Four vegetable samples, namely Swiss chard, carrot, tomato, green pepper, as well as paper wastewater were examined for heavy metal [Lead (Pb), Zinc (Zn), Cadmium (Cd), Iron (Fe), Copper (Cu), Chromium (Cr) and Cobalt (Co)] contamination using atomic absorption spectroscopy. The levels of Pb, Cd and Cr in paper wastewater were all above the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Addis Ababa is also experiencing discharges of wastewater from factories, containing pollutants without any treatment procedures being undertaken [8,11]. These pollutants may ultimately end up in the flood plain and agricultural lands of the southern Akaki-Kality Sub-City via transport by the rivers, which are crossing Addis Ababa [8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addis Ababa is also experiencing discharges of wastewater from factories, containing pollutants without any treatment procedures being undertaken [8,11]. These pollutants may ultimately end up in the flood plain and agricultural lands of the southern Akaki-Kality Sub-City via transport by the rivers, which are crossing Addis Ababa [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…People living in the Akaki catchment are using river water for irrigation, livestock watering, washing, cooking and other domestic needs [23], which may expose them to toxic heavy metals in the rivers. This is of concern, since various epidemiological studies have reported that exposure to toxic heavy metals is associated with health disorders and diseases including cardiovascular, gastrointestinal, nervous system, and kidney disease [12,15,[31][32][33][34][35][36][37][38]. Excess iron in the body leads to free radical formation through Fenton reaction, which causes adverse health effects including hemochromatosis, liver cirrhosis and siderosis [39].…”
Section: Introductionmentioning
confidence: 99%